Trends of Brain Drain in Remote Area of Nepal - Thapa, Kritika (Karnali Outlook: Knowledge Across Disciplines, 2026)
This article relies to a global phenomenon and is a highly debated topic on brain drain in rural people, to find out the impact of the respondents and challenges of the respondents of brain drain in migration. Issue of brain drain in Chaukune Rural Municipality, Surkhet district, is deeply tied to both economic challenges and aspirations for better futures abroad. However, the analysis also points to the resilience and potential of migrant contributions. A significant portion of remittance income is reinvested in education, local development, and health, demonstrating that migration, if managed wisely, can indirectly support development. Still, these benefits remain fragmented and are not a substitute for systemic, policy-driven improvements within Nepal. Hence, to reverse the trend of brain drain and harness its potential advantages, a multi-pronged, coordinated approach is needed. This includes economic development, institutional reform, quality education, and better utilization of migrant resources. The government, civil society, and international partners must work together to ensure that staying in Nepal becomes just as attractive as leaving.